Elementary school teachers’ experiences in engaging with digital technology in teacher professional development: The case of GeoGebra - Putra, Zetra Hainul; Lestari, Shindy; Siller, Hans Stefan (Journal on Mathematics Education, 2025)
Technological advances require teachers to be competent in utilizing them in mathematics learning. Teachers' success in teaching mathematics using digital technology cannot be separated from their mathematical and didactic knowledge. This study aims to reveal elementary school teachers' knowledge during their experiences in engaging with digital technology, GeoGebra, in teacher professional development programs. Data was obtained from the implementation of the Professional Development (PD) program in two schools, one in a private school focusing on the design of mathematical learning instruction integrated with GeoGebra and another in a public school focusing on the experimental process of teaching mathematics with GeoGebra. The data were analyzed using the Anthropological Theory of the Didactic (ATD) framework, specifically praxeology. The findings of this study reveal that elementary school teachers are aware of the need for theoretical aspects of a praxeology when designing mathematics learning instruction using GeoGebra in a PD program. Meanwhile, it is challenging for elementary school teachers to make use of GeoGebra instruction to support students' mathematical praxeologies. Therefore, the use of digital technology in teaching mathematics in elementary schools is still a significant challenge due to the mismatch between available technology and teacher needs.